Patient and nurse perspectives of a nurse-led community-based model of HIV care delivery in Malawi: a qualitative study - Odala Sande; Doris Burtscher; Daneck Kathumba; Hannock Tweya; Sam Phiri; Salem Gugsa (BMC, 2020)
Abstract Background Differentiated models of care (DMOC) are used to make antiretroviral therapy (ART) accessible to people living with HIV (PLHIV). In Malawi, Lighthouse Trust has piloted various DMOCs aimed at providing quality care while reducing personal and logistical barriers when accessing clinic-based healthcare. One of the approaches was community-based provision of ART by nurses to stable patients. Methods To explore how the nurse-led community ART programme (NCAP) is perceived, we interviewed eighteen purposively selected patients receiving ART through NCAP and the four nurses providing the community-based health care. Information obtained from them was complemented with observations by the study team. Interviews were recorded and transcribed. Data was analysed using manual coding and thematic analysis. Results Through the NCAP, patients were able to save money on transportation and the time it took them to travel to a health facility. Caseloads and waiting times were also reduced, which made patients more comfortable and gave nurses the time to conduct thorough consultations. Closer relationships were built between patients and care providers, creating a space for more open conversations (although this required care providers to set clear boundaries and stick to schedule). Patients' nutritional needs and concerns related to stigma remain a concern, while operational issues affect the quality of the services provided in the community. Considerations for community-led healthcare programmes include the provision of transportation for care providers; the physical structure of community sites (in regard to private spaces); the timely consolidation of data collected in the field to a central database; and the need for care providers to cover multiple facility-based staff roles. Conclusions The patients interviewed in this study preferred the NCAP approach to the facility-based model of care because it saved them money on transport, reduced waiting-times, and allowed for a more thorough consultation, while continuing to provide quality HIV care. However, when considering a community-level DMOC approach, certain factors - including staff transportation and workload - must be taken into consideration and purposefully planned.